Scaffold‐Free Tracheal Engineering via a Modular Strategy Based on Cartilage and Epithelium Sheets. Issue 6 (11th December 2022) - Yang, Minglei; Chen, Jiafei; Chen, Yi; Lin, Weikang; Tang, Hai; Fan, Ziwen; Wang, Long; She, Yunlang; Jin, Feng; Zhang, Lei; Sun, Weiyan; Chen, Chang
Abstract: Tracheal defects lead to devastating problems, and practical clinical substitutes that have complex functional structures and can avoid adverse influences from exogenous bioscaffolds are lacking. Herein, a modular strategy for scaffold‐free tracheal engineering is developed. A cartilage sheet (Cart‐S) prepared by high‐density culture is laminated and reshaped to construct a cartilage tube as the main load‐bearing structure in which the chondrocytes exhibit a stable phenotype and secreted considerable cartilage‐specific matrix, presenting a native‐like grid arrangement. To further build a tracheal epithelial barrier, a temperature‐sensitive technique is used to construct the monolayer epithelium sheet (Epi‐S), in which the airway epithelial cells present integrated tight junctions, good transepithelial electrical resistance, and favorable ciliary differentiation capability. Epi‐S can be integrally transferred to inner wall of cartilage tube, forming a scaffold‐free complex tracheal substitute (SC‐trachea). Interestingly, when Epi‐S is attached to the cartilage surface, epithelium‐specific gene expression is significantly enhanced. SC‐trachea establishes abundant blood supply via heterotopic vascularization and then is pedicle transplanted for tracheal reconstruction, achieving 83.3% survival outcomes in rabbit models. Notably, the scaffold‐free engineered trachea simultaneously satisfies sufficient mechanical properties and barrier function due to its matrix‐rich cartilage structure and well‐differentiated ciliated epithelium, demonstrating great clinical potential for long‐segmental tracheal reconstruction. Abstract : Schematic illustration of constructing a scaffold‐free complex tracheal substitute (SC‐trachea) via a modular strategy and the workflow for the tracheal reconstruction of rabbits. The scaffold‐free engineered trachea simultaneously satisfies sufficient mechanical properties and barrier function due to its matrix‐rich cartilage structure and well‐differentiated ciliated epithelium, demonstrating great clinical potential for long‐segmental tracheal reconstruction.